SOCIAL ISSUES IN THE SCHOOL ENVIRONMENT REGARDING THE DESTRUCTION OF SCHOOL FACILITIES - Lisnawati Lisnawati; Ahmad Hujaeni; Bakti Darmawan Arif Wiguna (PT Altin Riset Publishing, 2024)
This study examines social problems involving the destruction of school facilities. This phenomenon is increasing and causing concern in various educational institutions. This study aims to identify the factors that destroy school facilities, the most vulnerable school facilities to destruction and the awareness of all school residents not to be part of the destruction. The research method used is a quantitative approach with questionnaire data collection techniques. The research participants included all school residents at SMAN 1 Cibadak, SMAN 11 Pandeglang and SMAN 24 Tangerang Regency. The results of the study show that the factors that cause the destruction of school facilities by individuals include mere pranks. The next most domineering reason is accidentality; pleasures and dislikes; and as a form of venting anger. The facilities that are most vulnerable to damage are benches or classroom tables; toilets or sinks and school walls. This study recommends several measures to address this problem, such as increased supervision, the implementation of stricter discipline policies and character education programs that involve the active participation of students in maintaining and caring for school facilities. With a comprehensive and collaborative approach, it is hoped that a safer and more conducive school environment can be created for the educational process.